The Linguistic Image of the World on the Example of German and Polish Personal Insults with an Animalistic Component - Szczęk, Joanna (Respectus Philologicus, 2020)
The constant presence of animals in human life influences language. It is not only a rich animal and zoonotic lexis but also a way of perceiving animals, the attributes assigned to them and the behaviour observed. Through the prism of language, one can show the linguistic image of the world of a selected fragment of reality. The subject matter of this study is the linguistic image of the world based on personal insults with an animalistic component in German and Polish. The work is confrontational. The research corpus is constructed of personal zoonotic names collected from the dictionaries of both languages. The aim is to present the linguistic picture of the world based on the collected units and indicate, on this basis, the similarities and differences in the mentioned scope. Based on the analysis of the corpus, the appropriate conclusions are drawn about the perception of animals in both language cultures. Due to similar experiences in contact with animals, one can expect mainly similarities in this regard.